SBT-Living - Niklas Wikström (GBIF Sweden, 2010)
This dataset consists of data on living organism from the Bergius Botanical Garden, Stockholm. The living collections of the Bergius Botanical Garden - that is, the plants in the garden and in the conservatories, consist of thousands of publicly displayed species. The major sections are the herb garden, the botanic park with its various flower beds, the plantations of fruits and berries, the Edvard Anderson Conservatory with plants from the Mediterranean climate and the tropics, and the Victoria House with tropical and aquatic plants.
Keywords: Occurrence; Specimen; Occurrence; OCCURRENCE; Biological Sciences; Biologi